A comparative study between public and private organizations on structural factors and their impacts on managers’ career success - Mohd Rasdi, Roziah (2011)
This study examines the structural factors and managers’ career success (objective and subjective) and whether there are differences in these variables between the public and private sectors. A total of 497 samples from both public and private organizations were randomly selected for the study. Significant differences between the two sectors were found for managers’ objective career success and levels of perceived organizational support, but not for the subjective career success and organizational socialization. There are also differences in terms of the structural variables predicting public and private sectors managers’ objective career success. However, structural factors predicting both managers’ subjective career success are similar.